2006
DOI: 10.1007/s00737-006-0137-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of premenstrual syndrome and premenstrual dysphoric disorder in Japanese women

Abstract: To investigate the prevalence and impact of premenstrual symptoms in Japanese women, we developed the PSQ "The Premenstrual Symptoms Questionnaire" for the screening of premenstrual symptoms. The PSQ translates DSM-IV criteria into a rating scale with degrees of severity. One thousand one hundred and eighty-seven Japanese women between the ages of 20 and 49 yrs, who were seen at a clinic for uterine cancer screening, were assessed regarding their premenstrual symptoms using the PSQ. As many as 95% of these wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(150 citation statements)
references
References 10 publications
10
137
0
3
Order By: Relevance
“…Prevalences from 5 to 60% have been reported, with the highest rates seen in adolescent girls. 74,75 In a study of 313 women screened for PMS by questionnaires, women with PMS exhibited a greater number of 'episodes of eating' premenstrually than a control group. 32 Furthermore, women with PMS experienced more severe cravings than women who reported no PMS symptoms.…”
Section: Macronutrient Intake Food Cravings and The Premenstrual Synmentioning
confidence: 99%
“…Prevalences from 5 to 60% have been reported, with the highest rates seen in adolescent girls. 74,75 In a study of 313 women screened for PMS by questionnaires, women with PMS exhibited a greater number of 'episodes of eating' premenstrually than a control group. 32 Furthermore, women with PMS experienced more severe cravings than women who reported no PMS symptoms.…”
Section: Macronutrient Intake Food Cravings and The Premenstrual Synmentioning
confidence: 99%
“…16 However, this approach is timedemanding and may have reduced compliance, since a significant proportion of women refuse or do not properly fill the charts. 17,18 In addition, neither the DSM-IV nor the latest DSM-5 provide a set criteria or specifiers to determine PMDD severity. 19 To fill that gap, Steiner et al 16 have developed the Premenstrual Symptoms Screening Tool (PSST).…”
Section: Introductionmentioning
confidence: 99%
“…But this statistic is lower than the results of the study of Alavi et al, which had been done among the students of Bandar Abbas University of Medical Sciences University. Also, this statistic is significantly higher than the results of the study of Asiabar et al, (Kiani et al, 2009) and the studies done in Thailand and Japan (Chayachinda et al, 2008;Takeda et al, 2006). These data indicated that is spite of numerous questionnaires (retrospective and prospective), the prevalence of premenstrual syndrome in Iran is almost similar and higher than the extent observed from the other countries.…”
Section: Discussionmentioning
confidence: 61%
“…The exact reasons of difference in the prevalence of PMS among the women are unknown; but we can refer to some possible causes. These reasons can be the personal type (Björn et al, 2006;Fontana & Palfai 1994), hormonal changes, disorder in regulation of serotonin, diet, drugs and lifestyle (Takeda et al, 2006) and cultural differences.…”
Section: Discussionmentioning
confidence: 99%